2014
DOI: 10.1002/anie.201400946
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Activation with Chiral Nucleophilic Catalysts and N‐Haloimides: Enantioselective Iodolactonization of 4‐Arylmethyl‐4‐pentenoic Acids

Abstract: Chiral triaryl phosphates promote the enantioselective iodolactonization of 4-substituted 4-pentenoic acids to give the corresponding iodolactones in high yields with high enantioselectivity. N-Chlorophthalimide (NCP) is employed as a Lewis acidic activator and oxidant of I2 for the present iodolactonization. In combination with 1.5 equivalents of NCP, only 0.5 equivalents of I2 are sufficient to generate the iodinating reagent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
33
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(35 citation statements)
references
References 59 publications
1
33
0
1
Order By: Relevance
“…[4] They found that iodoperfluoroalkanes ( Figure 1) were abletoactivate quinoline derivatives and promote hydrogen transfer reactions with aH antzsch ester.F ollowing this breakthrough discovery,s everal groups reported that neutral and cationic iodoarenes were able to activate nitrogen-, oxygen-and halogen-containing electrophiles. [5,6] In most of these studies, cationic iodoarenes were used as catalysts, as these compounds activate organic molecules much more effectively than neutral iodoarenes. [7] The use of cationic iodoarenes is, however,n ot without disadvantages, as both their solubility and their stabilitya re generallyl ow.…”
mentioning
confidence: 99%
“…[4] They found that iodoperfluoroalkanes ( Figure 1) were abletoactivate quinoline derivatives and promote hydrogen transfer reactions with aH antzsch ester.F ollowing this breakthrough discovery,s everal groups reported that neutral and cationic iodoarenes were able to activate nitrogen-, oxygen-and halogen-containing electrophiles. [5,6] In most of these studies, cationic iodoarenes were used as catalysts, as these compounds activate organic molecules much more effectively than neutral iodoarenes. [7] The use of cationic iodoarenes is, however,n ot without disadvantages, as both their solubility and their stabilitya re generallyl ow.…”
mentioning
confidence: 99%
“…Therefore, the co‐presence of the oxidant (NBS) and the phosphine compound led us to wonder whether phosphine oxide generated in situ might be involved in the reaction. Sakakura, Ishihara, and co‐workers recently reported a chiral phosphate‐catalyzed iodolactonization reaction in which the P=O group is presumed to act as a Lewis base catalyst . Thus, we conducted the reaction of 1 a in CD 2 Cl 2 and measured the 31 P NMR spectrum of the crude mixture before workup (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The cooperation of hydrogen and halogen bonding also promotes the enantioselective iodolactonization of 4benzylpent-4-enoic acid with N-chlorophthalimide (NCP) in the presence of a chiral phosphate catalyst (CPC) (Scheme 18.23a) to give the corresponding iodolactones in high yields with high enantioselectivity [41]. In this reaction, the Lewis acidic NCP seems to activate I 2 through halogen bonding interactions in toluene at −40°C to form the active iodinating intermediate I (X = I; Scheme 18.23b), the presence of which is confirmed by Raman spectroscopy.…”
Section: Halogen Bonding Cooperation With Coordination or Hydrogen Bomentioning
confidence: 99%